Metode Elemen Hingga dan Elemen Batas untuk Antena Celah pada Pemandu Gelombang - Iswandi (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
In the higher frequency range, the wall-thickness causes more effects to the characteristic of slotted waveguide antenna. This paper presents numerical analysis of slotted waveguide antenna by incorporating the wall-thickness using finite element method for inner part of slot and boundary element method for outer or surface part. By using the field equivalent principle, the computation can be done only at the region of cut waveguide wall. The solution of those methods are employed to calculate the electric field along the slot surface and further use to calculate the equivalent network parameters of slot antenna. The results show the agreement to the published numerical and measurement results in the references.